Multimodal brain monitoring following traumatic brain injury: A primer for intensive care practitioners. (May 2022) - Casault, Colin; Couillard, Philippe; Kromm, Julie; Rosenthal, Eric; Kramer, Andreas; Brindley, Peter
Traumatic brain injury (TBI) is common and potentially devastating. Traditional examination-based patient monitoring following TBI may be inadequate for frontline clinicians to reduce secondary brain injury through individualized therapy. Multimodal neurologic monitoring (MMM) offers great potential for detecting early injury and improving outcomes. By assessing cerebral oxygenation, autoregulation and metabolism, clinicians may be able to understand neurophysiology during acute brain injury, and offer therapies better suited to each patient and each stage of injury. Hence, we offer this primer on brain tissue oxygen monitoring, pressure reactivity index monitoring and cerebral microdialysis. This narrative review serves as an introductory guide to the latest clinically-relevant evidence regarding key neuromonitoring techniques.